IL-18 Mediates Vascular Calcification Induced by High-Fat Diet in Rats With Chronic Renal Failure - Zhang, Yinyin; Zhang, Kun; Zhang, Yuling; Zhou, Lingqu; Huang, Hui; Wang, Jingfeng (Frontiers in Cardiovascular Medicine, 2021)
Objective: Vascular calcification (VC) is an important predictor of cardiovascular morbidity and mortality in patients with chronic renal failure (CRF). It is well-known that obesity and metabolic syndrome (OB/MS) predicts poor prognosis of CRF patients. However, the influence of OB/MS on VC in CRF patients isn't clear. IL-18 mediates OB/MS-related inflammation, but whether IL-18 is involved in OB/MS -mediated VC in CRF patients hasn't been studied. In this study, it was explored that whether OB/MS caused by high-fat diet (HFD) can affect the level of serum IL-18 and aggravate the degree of VC in CRF rats. Furthermore, it was studied that whether IL-18 induces rat vascular smooth muscle cells (VSMCs) calcification by activating the MAPK pathways. Approach: The rats were randomly assigned to the sham-operated, CRF and CRF + HFD groups. CRF was induced by 5/6 nephrectomy. Serum IL-18 levels and aortic calcification indicators were compared in each group. Primary rat VSMCs calcification were induced by β-glycerophosphate and exposed to IL-18. VSMCs were also treated with MAPK inhibitors. Results: The weight, serum levels of hsCRP, TG and LDL-C in CRF + HFD group were significantly higher than those in sham-operated and CRF groups (p < 0.05). Compared with the sham-operated group, the calcium content and the expression of BMP-2 of aorta in CRF and CRF + HFD groups were significantly increased (p < 0.05). Moreover, the calcium content and the expression of BMP-2 of aorta in CRF + HFD group was significantly higher than those in CRF group (p < 0.05). And the serum IL-18 level was positively correlated with aortic calcium content. It was also found that p38 inhibitor SB203580 can suppress the VSMCs calcification and osteoblast phenotype differentiation induced by IL-18. But the JNK inhibitor SP600125 can't suppress the VSMCs calcification and osteoblast phenotype differentiation induced by IL-18. Conclusions: These findings suggest that obesity-related inflammation induced by high-fat diet could exacerbate VC in CRF rats. Furthermore, serum IL-18 level had a positive correlation with the degree of VC. It is also found that IL-18 promoted osteogenic differentiation and calcification of rat VSMCs via p38 pathway activation.